2019
DOI: 10.2174/1573401314666180410142609
|View full text |Cite
|
Sign up to set email alerts
|

A Renewable Source as a Functional Food: Chia Seed

Abstract: Background: Chia seed is not a new food for humanity. The seed has been used in many different areas since the Aztecs, especially the food items. The chia seed is -becoming increasingly important because of its nutritional and functional properties and it is described as “the seed of the 21st century” and “new gold and super nutrient”. Background: In this review, general characteristics, nutritional composition, fields of usage, effects on health and importance in human nutrition of the chia seed have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Due to nutritional and health effects, chia seeds become more and more popular in many countries, especially across the Europe. Nowadays, they have found various applications, such as functional food, animal feed, and cosmetics [Dinçoğlu & Yeşildemir, 2019]. Some studies have shown their consumption to yield beneficial effects on such health problems as insulin resistance, dyslipidemia, cardiovascular diseases, or inflammation [Vuksan et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Due to nutritional and health effects, chia seeds become more and more popular in many countries, especially across the Europe. Nowadays, they have found various applications, such as functional food, animal feed, and cosmetics [Dinçoğlu & Yeşildemir, 2019]. Some studies have shown their consumption to yield beneficial effects on such health problems as insulin resistance, dyslipidemia, cardiovascular diseases, or inflammation [Vuksan et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Chia is a crucial ingredient for the development of functional food products (Dinçoğlu and Yeşildemir, 2019). The bioactive components found in chia seeds may be used to fortify food, besides being used as a vehicle for increasing the number or amount of vital nutrient intake (Coelho and Salas-Mellado, 2014).…”
Section: Chia Seeds As a Vehicle For Bioactive Components In Food Productsmentioning
confidence: 99%
“…This species was a cash crop in the centre of Mexico from 1500 to 900 BC. Chia was cultivated in the Central Valley of Mexico between 2000 and 2600 and was an important component of the Aztec diet (de Falco et al, 2017;Dincoglu and Yesildemir, 2019). Chia is a hardy annual plant and grows up to two meters high.…”
Section: Introductionmentioning
confidence: 99%
“…Chia is a hardy annual plant and grows up to two meters high. This plant adapts to a wide range of soils, climates and minimal rainfall (Dincoglu and Yesildemir, 2019). It starts owering at the age of 3 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation